Influence of increasing life expectancy to economic development. (Journal of Economic Research & Business Administration, 2015)
The article presents statistical data on the global trend of increasing life expectancy and decreasing birth rates in countries with different levels of development. Indicated the influence of the situation to the economic development, provides recommendations on some political reforms, which should be carried out.
Keywords: Indicated the influence of the situation; economic development